Prevalence of influenza vaccination and its association with health conditions and risk factors among Kansas adults in 2013: a cross-sectional study - Jeanie Santaularia; Wei Hou; Ghazala Perveen; Ericka Welsh; Babalola Faseru (BMC, 2016)
Abstract Background According to the Centers for Disease Control and Prevention, approximately 5-20 % of people are affected by influenza annually, and influenza causes more than 200,000 hospitalizations each year. The purpose of this study is to estimate the prevalence of influenza vaccination among high risk adults in Kansas. Methods The 2013 Kansas BRFSS data (n = 20,712) were analyzed to assess the prevalence of receiving influenza vaccination among Kansas adults, overall and for selected demographic characteristics within the past 12 months. Crude and adjusted prevalence rate ratios were computed using univariate logistic regression models with influenza vaccination as the dependent variable and health conditions or high risk groups as the main independent variables; these models were then adjusted for potential confounding. Results Overall, influenza vaccination rate was lower than the Healthy People 2020 target (42.2 % vs. 80 %). The prevalence of receiving influenza vaccination was higher among adults 65 years and older compared to adults 64 years and younger after adjusting for gender, annual household income, education, marital status, insurance status, and race/ethnicity. Similarly, the prevalence of receiving influenza vaccination was higher among adults who have current asthma, or have ever been diagnosed with diabetes, high blood pressure, cancer (excluding skin), and COPD compared to those who did not have these health conditions, as well as pregnant women compared to women who were not pregnant. Conclusions Although high risk groups have higher rates of influenza vaccination compared to low risk groups, more concerted efforts are needed to improve seasonal influenza vaccination in Kansas.